Testimonivm De Trinitate Vnivs Dei In Symbolo Apostolico: [Ienæ d. XX. Maii MDCCXXXX.] - Weissenborn, Jesaias Friedrich (Ritter, 1740)
Jena, Ankündigung zur Verteidigung einer theol. Diss. von Johann Christoph Pfeiffer, 1740